Rebranding the Seriality of Social Media Storytelling: Engagement with “Digital Rebranding and Quotidian Self-reinvention: Wellness Influencer-healers’ Negotiations of Authenticity and Tellability crises on Instagram” by Maxine Ali - Page, Ruth (Narrative Works, 2025)
Maxine Ali’s paper brings fresh focus to key areas of interest to mediated narrative analysis. In particular, rebranding offers us an important perspective on the seriality of identity work in social media contexts. In the last two decades, the research exploring personal storytelling on social media platforms has drawn attention to the episodic, open-ended forms of linearity (Ochs and Capps, 2001) that flourish in networked feeds of content which are continuously updated. As I have argued elsewhere (Page, 2013), the seriality of social media narration is varied and has analogous roots in pre-digital forms of storytelling. Nonetheless, the kinds of seriality that have drawn most attention in mediated narrative analysis have tended to privilege the episodic unfolding of events reported through successive posts within a single platform (see, for example, my own work (Page, 2012) which featured the analysis of Facebook status updates and tweets). This feed-centred seriality is characterised by “sharing the moment” (Georgakopoulou, 2017) and incorporated into the life-streaming practices common on social media (Marwick, 2013). Ali’s paper reminds us to look beyond the feed and take a narrative approach to the paratexts like profile information, which in their iterative updates must also be regarded as “serial and cumulative visual communication,” (Walker-Rettberg, 2014: 49).